Sobre la construcción de la identidad y la autonomía: un acercamiento a teorías de la formación - Echeverri Pérez, Luisa Fernanda (Educación, 2017)
To formulate basic principles within the reflexive theory of pedagogical action, we must differentiate between education and training, key issues of pedagogical reflection, in addition to venture into other categories such as person and citizen. According to this difference, these topics in the field of pedagogy do claim to potentiate an individual and social identity generating autonomy in being and exercising independent thinking. That is why this paper is anchored in Dietrich Benner proposals for addressing the first category, and the Latin American sociologist Hugo Zemelman for second, with the clear intention to present a defense of the capabilities and potential of the subject.